2020
DOI: 10.1039/c9ta12989h
|View full text |Cite
|
Sign up to set email alerts
|

Hollow PtCu nanorings with high performance for the methanol oxidation reaction and their enhanced durability by using trace Ir

Abstract: Cu atoms and a hollow structure are helpful for the improvement of the MOR activity of Pt. Trace Ir atoms might promise a superior durability for the Pt-based catalysts while maintaining the MOR catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Noble metals like Au, Pt, and Ag have emerged as highly active electrocatalysts compared to other non‐noble metal or metal oxides for methanol oxidation [10a,11b,20–21,30b,43] . However, few bimetallic alloys have been employed in methanol oxidation as cost‐effective catalysts [32b,34–35] . To explore the catalytic properties of the as‐prepared bimetallic Au/Cu nanocrystals were examined for their electrocatalytic efficiency towards the room‐temperature methanol oxidation reaction (MOR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noble metals like Au, Pt, and Ag have emerged as highly active electrocatalysts compared to other non‐noble metal or metal oxides for methanol oxidation [10a,11b,20–21,30b,43] . However, few bimetallic alloys have been employed in methanol oxidation as cost‐effective catalysts [32b,34–35] . To explore the catalytic properties of the as‐prepared bimetallic Au/Cu nanocrystals were examined for their electrocatalytic efficiency towards the room‐temperature methanol oxidation reaction (MOR).…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al. synthesized Hollow PtCu nanorings which exhibited excellent activity for the methanol oxidation reaction [34] . They found that the durability of Pt 0.75 Cu alloy nanorings for MOR is significantly increased by doping trace Ir.…”
Section: Introductionmentioning
confidence: 99%
“… 63 The efficiency of a catalyst can be judged based on the following parameters: (a) anodic peak current density ( I ap ) at respective anodic potential ( E ap ), (b) onset potential ( E onset ), showing methanol oxidation activity, and (c) the forward to reverse peak current density ( I f / I r ) ratios, reflecting the catalyst tolerance. 64 As can be seen in Table 2 and Table S3 , the I ap of the synthesized catalysts toward MOR is in the order of Pt 1 Cu 1 > Pt 1 Ni 1 > Pt 1 Fe 1 > Pt 1 Zn 1 > Pt 1 Co 1 . The catalysts Pt 1 Cu 1 /PC 950, Pt 1 Ni 1 /PC 950, Pt 1 Fe 1 /PC 950 and Pt 1 Zn 1 /PC 950 have higher I ap values, while Pt 1 Co 1 /PC 950 have comparable I ap values to those of the commercial Pt/C 20% catalyst (0.33 mA cm Pt −2 ).…”
Section: Resultsmentioning
confidence: 85%
“…Significantly, the MOR electrochemical performance of Pt 1 Cu 1 aerogels have been improved after the introduction of Ir, clearly indicating the promoting role of Ir on PtCu in MOR. Moreover, the MOR activity of Pt 1 Cu 1 Ir 0.04 aerogels is far more superior compared with that of the most reported Pt-based catalysts (Figure d). ,, …”
Section: Resultsmentioning
confidence: 88%
“…introduced to PtCu have been proven to be an efficient strategy to improve the MOR performance . Besides, Ir is the most active non-Pt metal for MOR that has been proven. Inspired by this, regulating the composition of electrocatalysts has generated enormous effects in improving the MOR stability on account of their electronic/synergistic or geometric effects. Therefore, the development of highly stable electrocatalysts based on component engineering for MOR deserves extensive researches.…”
Section: Introductionmentioning
confidence: 99%